Research on Automatic Tool Delivery for CNC Workshop of Aircraft Equipment Manufacturing. (May 2019) - Zeng, Ping; Wu, Fei; Zhi, Tongxing; Xiao, Le; Zhu, Shaowei
Abstract: Aiming at the inefficiency of tool distribution in CNC workshop of aircraft equipment manufacturing, and adapting to the particularity of distribution without large network environment, The solution of intelligent tool delivery using AGV based on machine vision and QR Code navigation is proposed. Image processing of AGV path ribbon, path navigation error analysis and QR Code position calibration are studied in the planned path to achieve machine vision plus QR Code redundant navigation positioning. The AGV can complete the accurate loading and unloading tool of the robot library through the QR Code interaction mode with the machine tool. To realize automatic distribution of tool in CNC workshop of aircraft equipment manufacturing.